Moderated by personal perception: The preventive relationship between home HIIT dance and depression during the COVID-19 pandemic in China - Hu, Yifan; Son, KwanJung; Yang, Zheng; Mao, Yufei (Frontiers in Public Health, 2023)
Lockdowns during the COVID-19 pandemic were believed to greatly increase the risk of depression among isolated residents, in both China and Western countries. How to effectively reduce this risk has become one of the key issues in the field of public mental health. The present study seeks to examine the preventive effects of doing home HIIT dance – which became popular during Shanghai’s COVID-19 lockdown in 2022 – on depression, and how such preventive effects have been mediated by different personal perception factors. The preventive effects of doing home HIIT dance on depression was differently mediated by residents’ personal perception factors, such as perceived benefits, severity, and self-efficacy, based on the health belief model. These results deepen the research on the psychological effects of doing home HIIT dance on preventing depression, especially in the COVID-19 lockdown period, emphasizing the possible moderation effects of different self-perception factors.